Effectiveness of Gastric Cancer Screening on Gastric Cancer Incidence and Mortality in a Community-Based Prospective Cohort - Kim, Heewon; Hwang, Yunji; Sung, Hokyung; Jang, Jieun; Ahn, Choonghyun; Kim, Sang Gyun; Yoo, Keun-Young; Park, Sue K. (Cancer research and treatment, 2018)
This study was performed to investigate the effectiveness of gastric cancer (GC) screening methods in a community-based prospective cohort of the Korean Multi-center Cancer Cohort (KMCC) with over a 10-year follow-up. A total 10,909 and 4,773 subjects from the KMCC with information on gastroendoscopy (GE) and upper gastrointestinal series (UGIS) were included in this study. Cox proportional hazard model adjusted for age, sex, infection, cigarette smoking, and alcohol drinking was used to estimate the hazard ratios (HRs) and 95% confidence interval (CI). The GE screened subjects had almost half the risk of GC-specific death than that of unscreened subjects (HR, 0.58; 95% CI, 0.36 to 0.94). Among the GC patients, GE screenees had a 2.24-fold higher survival rate than that of the non-screenees (95% CI, 1.61 to 3.11). In particular, GE screenees who underwent two or more screening episodes had a higher survival rate than that of the non-screenees (HR, 13.11; 95% CI, 7.38 to 23.30). The effectiveness of GE screening on reduced GC mortality and increased survival rate of GC patients was better in elderly subjects (≥ 65 years old) (HR, 0.47; 95% CI, 0.24 to 0.95 and HR, 8.84; 95% CI, 3.63 to 21.57, respectively) than that in younger subjects (< 65 years old) (HR, 0.66; 95% CI, 0.34 to 1.29 and HR, 1.83; 95% CI, 1.24 to 2.68, respectively). In contrast, UGIS screening had no significant relation to GC mortality and survival. The findings of this study suggest that a decreased GC-specific mortality and improved survival rate in GC patients can be achieved through GE screening.